Tom, Tom, the piper's son [1969-1971] - Jacobs, Ken ([s.l.] : Reframe, 2008)
This DVD release of the silent experimental film by Ken Jacobs begins by presenting the entire eight-shot, 10-minute 1905 short film Tom, Tom, the piper's son originally produced by American Mutoscope and Biograph Company. The filmmaker then rephotographs it in detail; some segments are run in slow motion, some enlarged, some in freeze frame, etc. Two color sequences were also added.
Includes the short film A Tom Tom chaser (11 min.), improvised with Scot Olive in 2002.
film
Keywords: Jacobs, Ken, -- 1933-